Normatywizacja tożsamości zbiorowej w preambułach do konstytucji państw postkomunistycznych - Młynarska-Sobaczewska, Anna (Filozofia Publiczna i Edukacja Demokratyczna, 2013)
Preambles are parts of constitutions, which are visibly neglected in legal theory and constitutional law. They are defined as solemn introductions to constitutions, which indicate the sovereign, historical and political context of increasing the new constitutional order, main aims and principles – the foundation of constitution. Such elements are also commonly apparent in most of post communist constitutions of European states. The article shows the integrative function of these preambles, achieved by using clauses creating and maintaining the identity of political community. The clauses with this function are identified as: statements regarding national and cultural heritage, declaration of sovereign as people or nation, and expression of common aims and fundamental principles of community. The article investigates these elements in texts of preambles to post-communist constitutions and indicates their role as tending to create the national identity.